Service Quality Orientation at the Faculty of Tarbiyah and Keguruan Sciences UINSI Samarinda - Pahmi Rumaidi; Fitri Sakina Ramadani; Achmad Ruslan Afendi (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
The aim of this research is to gain insights into the service quality orientation at the Faculty of Tarbiyah and Keguruan Sciences (FTIK) at UINSI Samarinda. This study is a descriptive qualitative research that utilizes primary and secondary data sources, as well as data collection techniques such as observation, interviews, and documentation. The data analysis methods used include data condensation, presentation, and conclusion drawing. The study's validity is ensured through triangulation of sources and methods. The findings reveal that FTIK UINSI Samarinda has fulfilled four quality processes, including planning, implementation, monitoring and evaluation, and development. These processes were found to be carried out by the FTIK leadership in accordance with the UIN Samarinda campus procedures and the FTIK's existing guidelines and SOPs.